2017
DOI: 10.1016/j.jtho.2017.01.002
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Postoperative Radiotherapy for Thymoma and Thymic Carcinoma

Abstract: In this large database analysis of PORT for thymic tumors, PORT was associated with longer OS, with the greatest relative benefits observed for stage IIB to III disease and positive margins. In the absence of randomized studies assessing the value of PORT, these data may inform clinical practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
88
3
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 106 publications
(100 citation statements)
references
References 35 publications
7
88
3
2
Order By: Relevance
“…The use of postoperative radiation for stage II thymomas remains controversial. Jackson et al demonstrated that younger age, early Masao–Koga stage, chemotherapy, and postoperative radiation were independently associated with longer OS in patients with thymomas . In contrast, we observed that postoperative radiation is not independently associated with longer OS.…”
Section: Discussioncontrasting
confidence: 84%
See 2 more Smart Citations
“…The use of postoperative radiation for stage II thymomas remains controversial. Jackson et al demonstrated that younger age, early Masao–Koga stage, chemotherapy, and postoperative radiation were independently associated with longer OS in patients with thymomas . In contrast, we observed that postoperative radiation is not independently associated with longer OS.…”
Section: Discussioncontrasting
confidence: 84%
“…Jackson et al demonstrated that younger age, early Masao-Koga stage, chemotherapy, and postoperative radiation were independently associated with longer OS in patients with thymomas. 14 In contrast, we observed that postoperative radiation is not independently associated with longer OS. Consistent with the results of a Chinese study, we also observed that postoperative radiation is not an independent prognostic factor of OS.…”
Section: Discussioncontrasting
confidence: 68%
See 1 more Smart Citation
“…The role of adjuvant RT after complete resection in Masaoka stage II disease is controversial (26). Recently, well powered large sized studies showed increase in OS in Masaoka stage II and III thymoma with adjuvant RT (9,26,27).…”
Section: Discussionmentioning
confidence: 99%
“…The role of adjuvant RT after complete resection in Masaoka stage II disease is controversial (26). Recently, well powered large sized studies showed increase in OS in Masaoka stage II and III thymoma with adjuvant RT (9,26,27). Radiotherapy planning should be established cautiously in adjuvant setting in terms of benefit versus toxicity, since thymomas grow in close proximity to critical organs (28).…”
Section: Discussionmentioning
confidence: 99%